Motilitas dan vitalitas spermatozoa manusia post freezing setelah simpan beku dengan medium TES-Tris yolk citrat yang dimodifikasi dengan jenis kuning telur berbeda - Djaelani, Muhammad Anwar (Bioma : Berkala Ilmiah Biologi, 2012)
The aim of this research was to examine the possibility of semen cryopreservation using modified TES-Tris yolk citrat (TES-TYC) medium with different egg yolk. Semen fulfilling inclusion  criteria with WHO  criteria was divided into three groups and the sperm motility and vitality was counted as initial data. The semen was then mixed with TES-TYC medium with chicken egg yolk, TES-TYC medium with duck egg yolk and TES-TYC medium with goose egg yolk then cryopreserved in liquid nitrogen. After one mounth the semen was thawed and recount its sperm motility and vitality. Data obtained showed that the motility and vitality of  post freezing sperm cryopreserved with TES-TYC medium with chiken was higher compared to the other medium. It could be concluded that the existenced of chicken egg yolk in TES-TYC medium was better kept sperm integrity during cryopreservation compared with the other medium, hence the existenced of egg yolk as ingredient in TES-TYC medium should be chicken egg yolk.   Key words : motilitas dan vitalitas, medium TES-Tris yolk citrat, kuning telur